(untitled) (Fiep Bulletin - online, 2014)
This study aimed to verify the Methodology Applied in Physical Education Classes for Children with Down Syndrome (DS ). The study is a qualitative exploratory and descriptive. Three schools of São Luís - MA constitute the universe of this research: public school, private and philanthropic. The sample was composed of eight teachers, therefore, a teacher of the institution of public education, three of four from the private and philanthropic institution. We used a questionnaire with six open questions, with the intention to examine these methodologies on which teachers use to teach their classes. However, only six teachers surveyed responded and returned the questionnaires, while others not returned. However realizes the importance of this research is to investigate teachers apply these methodologies to facilitate a theoretical basis in their classrooms with children SD. Taking into consideration that the whole methodology goes against what the literature addresses: plan, schedule and use up a pedagogical intervention or action.